3x-2y=5
5x-y=3
Solve by substitution method
Answers
Answered by
20
▶ Question : (3x-2y=5 ; 5x-y=3) Solve by substitution method
▶ Explanation :-
=> 3x - 2y = 5 -------- ( 1 )
=> 5x - y = 3 --------- ( 2 )
=> 5x - y = 3
=> 5x = 3 + y
=> x = 3 + y / 5 -------- ( 3 )
Substituting eq ( 3 ) in eq ( 1 )
=> 3 ( 3 + y / 5 ) - 2y = 5
=> 9 + 3y / 5 - 2y = 5
=> 9 + 3y - 10y / 5 = 5
=> 9 - 7y = 5 × 5
=> 9 - 7y = 25
=> - 7y = 16
=> y = - 16 / 7
Substituting value of y in eq ( 3 )
=> x = 3 + ( - 16 / 7 ) / 5
=> x = 3 - 16 / 7 /5
=> x = 21 - 16 / 35
=> x = 5 / 35
=> x = 1 / 7
2001vandanasingh:
Thanks nd rating glt dal gai so sorry
Answered by
8
Answer:
Step-by-step explanation:
Similar questions
Social Sciences,
8 months ago
Geography,
8 months ago
Social Sciences,
1 year ago
Biology,
1 year ago
Chemistry,
1 year ago
Math,
1 year ago